Twist springback measurement of autonomous underwater vehicle propeller blade based on profile deviation - Abdullah, Ahmad Baharuddin; Salit, Mohd Sapuan; Samad, Zahurin; M. Tandoor, Khaleed Hussain; Abdul Aziz, Nuraini (Science Publications, 2013)
Geometrical defects that are attributable to springback are among the major defects induced by the sheet metal forming process. Such defects are critical for sections with varying thickness, such as Autonomous Underwater Vehicle (AUV) propeller blades. In this study, the springback in the twist-bending of an AA6061 propeller blade was quantified by comparing the targeted and manufactured profiles obtained using the commercial three-dimensional surface measurement technique. The results show that the twist springback becomes larger as the twist angle increases. Similarly, the twist springback increases with increasing deformation ratio.